Similarities and Differences in Adolescents' Organized and Civic Activity Networks across Rural and Non-Rural Communities. - Oosterhoff, Benjamin; Metzger, Aaron; Alvis, Lauren (Journal of Youth & Adolescence, 2020)
Youth are often involved in multiple organized and civic activities simultaneously, resulting in complex patterns or "networks" of participation. Little research has examined the network structure of adolescents' organized and civic participation and whether these networks vary across communities. Examining activity networks may help identify specific forms of participation that are more widely and strongly connected with other activities, and may thus provide a gateway for becoming multiply involved. Youth (N= 902; M = 15.90; 55.7% female) from a rural (n= 476) and non-rural (n= 426) community completed measures assessing engagement in 25 civic and organized activities. Network analysis indicated that activities in the rural community had greater network density relative to the non-rural community. Volunteering to clean up the neighborhood was most central to both networks. Church attendance and community sports were more central for the rural network, whereas protesting and school arts were more central for the non-rural network. These findings suggest that volunteer activities may serve as a "hub" for organized and civic activity participation and highlight similarities and differences in the co-occurrence of activities across two distinct communities.